Budaya Maritim dan Diplomasi Maritim untuk Kepentingan Nasional - Hanggarini, Peni; Madjid, M. Adnan; Perwita, Anak Agung Banyu; Wiranto, Surya (Universitas Diponegoro, 2022)
This paper discusses how pillars in Indonesia’s vision of Global Maritime Fulcrum (GMF) are interrelated, particularly maritime culture and maritime diplomacy. These two pillars need to be implemented as an entity concept. Previous literatures have mainly discussed how each of the pillars contribute to the realization of GMF vision. Based on the perspectives of International Relations theory, this paper explains how maritime culture can influence the formulation of strategy and implementation of Indonesia’s maritime diplomacy. The authors argue that the pillars of maritime culture and maritime diplomacy are reflection of the national interests supporting the GMF vision. Additionally, the embedded maritime culture in Indonesian society can have positive implications for the inputs, processes, outputs, and outcomes of maritime diplomacy. If maritime culture can be managed, it would serve as an instrument of soft power, it would construct the national identity and it would drive the creation of regional security governance, maritime norms and regime that could serve as facilitating factors for the achievement of national interests through Indonesia’s maritime diplomacy. The pillar of maritime culture is the root of maritime diplomacy for achieving national interests.